Buyer’s Legal Protection in Absolute Power of Attorney for Paid-Off Land - Putri, Andi Wika; Yuhelson; Halim, Anriz N. (Ilmu Hukum, Sharia and Law Faculty, Sunan Gunung Djati Islamic State University of Bandung, 2025)
Abstract: The use of absolute power of attorney (Kuasa Mutlak) in land Sale and Purchase Agreements (PPJB) still common in Indonesia, despite legal risks. Even after full payment, land ownership cannot be transferred without a Sale and Purchase Deed (AJB) and registration at the National Land Agency (BPN). While absolute power of attorney offers a quick solution, it violates contract principles and legal regulations, including the Minister of Home Affairs Instruction No. 14/1982. This study examines two key issues: (1) the legal consequences of absolute power of attorney in fully paid PPJBs, and (2) the mechanisms for protecting buyers in such cases. Through a normative analysis of court rulings and legal literature, the findings show that absolute power of attorney fails to secure buyer rights and often leads to disputes. To mitigate risks, stronger contractual clauses, stricter notarial oversight, and limited special power of attorney are proposed. The study recommends regulatory harmonization and public legal education to ensure safer and fairer land transactions.